Rancang Bangun Sistem Informasi Berbasis Database dalam Pengelolaan Data Guru dan Siswa Sekolah Menengah Atas - Rohmatillah, Rohmatillah (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2023)
This research aims to present the design of a database-based information system in managing teacher and student data at Ulul Al-Baab High School Sukabumi, West Java. The method used in collecting data for the purposes of designing the system in this research is using interviews, literature studies, and prototypes. The results of the research show that at least the website can help the Ulul Al-Baab Senior High School, Sukabumi, West Java, in implementing teacher and student data management, which was initially done manually and can now be done online via the utilization website. Having this website can at least help you input data more efficiently and you will no longer be afraid of losing data due to unexpected things.